INSTITUSIONALISASI KURIKULUM BERBASIS CINTA DALAM MEMBANGUN EKOSISTEM PENDIDIKAN KARAKTER DI MADRASAH IBTIDAIYAH MIFTAHUL FAKHIRIN MELALUI INTEGRASI BUDAYA SEKOLAH DAN PEMBIASAAN RELIGIUS - Hariyanto; Ach. Maimun; Muhammad Afan; Atiqur Rahman Binuri Ramadan; Moh. Ali Mahdi (Jurnal Ikhtibar Nusantara, 2026)
This study aims to analyze the institutionalization of the Love-Based Curriculum (Kurikulum Berbasis Cinta/KBC) in building a character education ecosystem at MI Miftahul Fakhirin, Kadur, Pamekasan, through the integration of school culture and religious habituation. Institutionalization is defined as the embedding of values, norms, and practices into the organizational structure of the school so that they no longer depend on particular individuals. Using a descriptive qualitative single-case study design, data were collected from curriculum documents, institutional records, and observations of daily, weekly, and annual habituation programs, and analyzed following the interactive model of Miles, Huberman, and Saldana (2014). The findings indicate that KBC institutionalization is supported by three main pillars, namely exemplary leadership by the headmaster and teachers, structured religious habituation, and local-national cultural integration, which operate through three interrelated institutional mechanisms: regulative, normative, and cognitive-cultural. Based on these findings, this study proposes a conceptual model termed the Multi-Mechanism Institutionalization of Love-Based Curriculum (IM3-KBC) as a theoretical contribution to the study of character curriculum institutionalization in madrasah. The synergy of these pillars and mechanisms forms a multi-layered character education ecosystem encompassing spiritual, social-emotional, national, and intellectual dimensions. The study recommends strengthening habituation monitoring instruments to ensure sustainable evaluation of the institutionalization process.